The Effect of Changes in Layers of Taxable Income Article 17 of the Law on Cost of Goods Sold, Reporting of Individual Tax Returns and Taxpayer Awareness of Income Tax Receipt at the Pratama Sawah Besar One Tax Service Office - Novianita Rulandari; Salsabila Rahmayani (Yayasan Ilomata, 2023)
This study aims to determine the magnitude of the influence of changes in layers of taxable income Article 17 of the HPP Act, reporting of individual tax returns and awareness of taxpayers simultaneously on income tax receipts at KPP Pratama Sawah Besar One. This study used a quantitative method by distributing questionnaires to 145 respondents and using a purposive sampling technique. Data analysis was carried out by validation test, reliability test, classic assumption test, then the data was tested by multiple linear regression analysis, T test, F test, correlation coefficient (R), and coefficient of determination (R2). The results of this study are based on testing the hypothesis by using the T test and F test, changes in layers of taxable income under Article 17 of the HPP Law, individual SPT reporting and taxpayer awareness have a positive and significant effect on income tax receipts. The test results of the coefficient of determination (R2) of 0.883 can be stated that the Effect of Changes in Layers of Taxable Income Article 17 of the HPP Law (X1), Individual SPT Reporting (X2) and Taxpayer Awareness (X3) on Income Tax Receipts (Y) is 88.3%, the remaining 11.7% is influenced by other variables not examined in this study.